Perceived quality of distance education during the COVID-19 pandemic by postgraduate students of a school of medicine - Izaguirre, Manuel (2023)
Introduction. When the government decreed the mandatory quarantine during the COVID-19 pandemic, a new way of exercising the pedagogical work in a synchronous or asynchronous way was initiated. Objectives. To know through the levels of dissatisfaction the perceived quality of distance education during the COVID-19 pandemic by postgraduate students. Methods. A descriptive observational study was carried out. The population consisted of 403 students, the variables were perceived quality and distance education. Descriptive statistics analysis and univariate analysis were applied. Results. Level of satisfaction with the perceived quality of distance education of the 413 students was indifference in 45.7%, dissatisfaction in 12.5% and satisfaction in 41.8%. The level of satisfaction of perceived quality corresponded mostly to the virtual learning environment and information received and content of the virtual classroom, while the highest level of indifference corresponded to distance education (78%), neuropedagogy (51.1%) and teacher (45.8%). Conclusions. Satisfaction responded to the environment, information, and materials, while dissatisfaction to the adaptation of pedagogical strategies and materials to virtuality.